Fibrocytes in the Pathogenesis of Chronic Fibrotic Lung Disease - Loomis-King, Hillary (Curr Respir Med Rev, 2013)
Fibrocytes were initially described in 1999 and since that time there has been a growing body of literature to suggest their importance in a number of chronic lung diseases. It is now well established that fibrocytes derive from the bone marrow and circulate within the peripheral blood. However, when injury occurs, fibrocytes can travel to the site of damage via chemokine-mediated recruitment. Recent studies suggest that fibrocyte numbers increase within the lung or circulation during numerous disease processes. Although fibrocytes readily differentiate into fibroblasts in vitro, whether they do so in vivo is still unknown. The variety of pro-fibrotic mediators that are secreted by fibrocytes makes it likely that they act via paracrine functions to influence the behavior of resident lung cells. This review summarizes recent insights regarding fibrocytes in asthma, scleroderma and IPF.